RAGAM BAHASA SAPAAN DALAM BAHASA DAYAK BAKATI"™ DI KELURAHAN SEBALO KECAMATAN BENGKAYANG - Agesti, Priskila; Patriantoro, Patriantoro; Sanulita, Henny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research aims to classify data obtained from the field, conduct data inventory on various types of greetings, usage, and functions of greetings, as well as plans for implementation in Indonesian language learning based on the variety of greetings in Dayak Bakati"™ language in Sebalo Village, Bengkayang Sub-district. The method used in this research is descriptive method. The form of this research is qualitative. The data source in thisresearch isthe Dayak Bakati"™ community residing in Sebalo Village. Data collection techniques include observation, recorded interviews, note-taking, and documentation. Data collection tools include recording and documentation devices, writing tools, questionnaires, and note sheets. The techniques for validating the data are diligent observation, sufficient references, and discussion with peers. This research produced 34 data of greetings in Dayak Bakati"™language in Sebalo Village, Bengkayang Sub-district with details of indefinite personal name greetings but detailed in the data are 1 data, personal pronoun greetings amounted to 2 data, kinship greetings 13 data, and nonkinship greetings 8 data, rank and position greetings 6 data, and professional greetings 4 data. Also, the functions of greetings in the Dayak Bakati"™ community in Sebalo Village, Bengkayang Sub-district. The form of Indonesian language learning text based on greetings in Dayak Bakati"™ language in Sebalo Village, Bengkayang Sub-district is descriptive text.